2013
DOI: 10.1371/journal.pone.0053781
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Annotation and Developmental Expression of the Chicken Intestinal MUC2 Gene

Abstract: Intestinal mucin 2 (MUC2) encodes a heavily glycosylated, gel-forming mucin, which creates an important protective mucosal layer along the gastrointestinal tract in humans and other species. This first line of defense guards against attacks from microorganisms and is integral to the innate immune system. As a first step towards characterizing the innate immune response of MUC2 in different species, we report the cloning of a full-length, 11,359 bp chicken MUC2 cDNA, and describe the genomic organization and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 51 publications
(89 reference statements)
2
32
0
Order By: Relevance
“…Another gene indirectly related to inflammation is MUC2, the most abundant mucin in the intestine. The low expression of MUC2 observed in the present study is believed to also contribute to inflammation as its deficiency has been reported to increase bacterial translocation and inflammation [38]. In line with MUC2 expression, the very dry aspect of feces suggested that the mucus was severely compromised and could not play its role as a layer of protection in the intestine.…”
Section: Discussionsupporting
confidence: 62%
“…Another gene indirectly related to inflammation is MUC2, the most abundant mucin in the intestine. The low expression of MUC2 observed in the present study is believed to also contribute to inflammation as its deficiency has been reported to increase bacterial translocation and inflammation [38]. In line with MUC2 expression, the very dry aspect of feces suggested that the mucus was severely compromised and could not play its role as a layer of protection in the intestine.…”
Section: Discussionsupporting
confidence: 62%
“…Besides tight junction proteins, mucins produced by Goblet cells form the first line of defense in maintaining intestinal barrier (57). Mucin-2 is the main mucin produced and is considered a biomarker of intestinal health because it avoids microbial adhesion to the mucosa (58,59). In the present study, broilers on challenged control group had the MUC2 expression downregulated compared to broilers on non-challenged and P(OA+EO) groups.…”
Section: Discussionmentioning
confidence: 54%
“…Evolutionary studies suggest that mucins share a common ancestor, since their domain structures are well conserved in metazoans ( 71 , 81 ). All mucins (MUC) contain at least one PTS domain, a region rich in proline, threonine, and serine ( 18 , 82 ). Chicken MUC2 has been reported to be remarkably similar to human and mouse outside of the central PTS domain, but is highly divergent within this central repetitive structure ( 82 , 83 ).…”
Section: Discussionmentioning
confidence: 99%